Characteristic Influence of Cerium Ratio on PrMn Perovskite-Based Cathodes for Solid Oxide Fuel Cells - Balkanli Unlu, Esra; Karaismailoglu Elibol, Meltem; Figen, Halit Eren (MDPI, 2025)
In this study, cerium with different ratios (x = 0 (zero), 0.1, 0.15, 0.5) was added to the PrMn structure as an A-site material to evaluate characteristic behavior as a potential cathode material for solid oxide fuel cells. The PrxCe1-xMnO3-delta electrocatalysts were synthesized using the sol-gel combustion method and were assessed for their electrochemical, phase, and structural properties, as well as desorption and reducibility capabilities. Phase changes, from orthorhombic to cubic structures observed upon cerium additions, were evaluated via the X-Ray diffraction method. X-Ray photoelectron spectroscopy (XPS) showed the valence states of the surface between the Ce4+/Ce3+ and Pr4+/Pr3+ redox pairs, while oxygen temperature programmed desorption (O2-TPD) analysis was used to evaluate the oxygen adsorption and desorption behavior of the electrocatalysts. Redox characterization, evaluated via hydrogen atmosphere temperature-programmed reduction (H2-TPR), revealed that a higher cerium ratio in the structure lowered the reduction temperature, suggesting a better dynamic oxygen exchange capability at a lower temperature for the Pr0.5Ce0.5MnO3-delta catalyst compared to the electrochemical behavior analysis by the electrochemical impedance spectroscopy method. Moreover, the symmetrical cell tests with Pr0.5Ce0.5MnO3-delta electrodes showed that, when combined with scandia-stabilized zirconia (ScSZ) electrolyte, the overall polarization resistance was reduced by approximately 28% at 800 degrees C compared to cells with yttria-stabilized zirconia (YSZ) electrolyte.
Keywords: solid oxide fuel cell; scandia-stabilized zirconia; praseodymium catalyst; PrCeMn; cathode; electrolyte comparison; CHEMICAL-PROPERTIES; MIXED OXIDES; ELECTROCHEMICAL PERFORMANCE; RARE-EARTH; TEMPERATURE; PRASEODYMIUM; CATALYSTS; TECHNOLOGIES; ELECTROLYTE; REDUCTION; Chemistry